THE EFFECT OF PARENTS ROLE ON STUDENT'S LEARNING OUTCOMES WHEN PANDEMIC COVID-19 ERA ON SOCIAL SCIENCE SUBJECT IN 8th GRADE OF JUNIOR HIGH SCHOOL AL-FALAH BEKASI - Silatur rahmi; Nadia Rista (Lembaga Penelitian dan Pengabdian Kepada Masyarakat STKIP Ahlussunnah, 2021)
Learning at home or E-learning is carried out to stop the spread of Covid-19 disease. This study is aim to determine the effect of parent’s role (X) on learning outcomes (Y) at Junior High School Al-Falah, Bekasi in 8th grade on sosial studies subject. This research method used a descriptive survey. The research used a random sample of 71 students. The conclusion of the research revealed: 1) The linear regression equation obtained Y= 37.824 + 0.513X, its mean that the Y score can be predicted through a linear equation. 2) From the results of the analysis, it can be seen that the role of parents affects social studies outcomes, this can be seen from the thit and p-value less than 0.05. Therefore, it can be interpreted that the influence of parent’s role has a positive effect on social studies outcomes. 3) From the results of the analysis of the significance test of the regression equation, it is obtained that thit and p-value is less than 0.05, or Ho is rejected. Thus the Y or X regression is significant or the role of parents affects the learning outcomes of social studies subjects. 4) The significance test of the correlation coefficient is obtained = 0.428 with a small p-value of 0.05, this means Ho is rejected. Thus the coefficient is moderately correlated between the Role of Parents and Social Studies Outcomes . Meanwhile, from the analysis results obtained RSquere 0.183, which implies that 18.3% of the variation of the results of the parental role on learning outcomes.